War in Ukraine and Western sanctions: How vulnerable are German firms? - Holger Görg; Anna Jacobs; Saskia Meuchelböck (Kiel Institute for the World Economy (IfW Kiel), 2022)
Russia's invasion of Ukraine has led to a sudden reassessment of political and economic relations with Russia, including financial and trade relations. This policy brief analyzes a new firm-level dataset for Germany to examine the involvement of German firms in the Russian and Ukrainian markets. We analyse the impact of the annexation of Crimea and related sanctions in 2014 and identify the degree and shape of vulnerability of German trade with respect to these two markets on the firm level. The firm-level data reveals that Russia and Ukraine have become less important as trading partners at both the extensive margin and the intensive margin. So far, recovery effects have been observed merely for German-Ukrainian trade. Within the group of firms trading with Russia and Ukraine, we see a clear heterogeneity, which in turn is reflected in individual vulnerability towards the affected markets. – – Der Einmarsch Russlands in die Ukraine hat zu einer plötzlichen Neubewertung der politischen und wirtschaftlichen Beziehungen zu Russland geführt, einschließlich der Finanz- und Handelsbeziehungen. In diesem Policy Brief wird ein neuer Datensatz auf Unternehmensebene für Deutschland analysiert, um das Engagement deutscher Unternehmen auf dem russischen und ukrainischen Markt zu untersuchen. Wir analysieren die Auswirkungen der Annexion der Krim und der damit verbundenen Sanktionen im Jahr 2014 und ermitteln den Grad und die Form der Vulnerabilität des deutschen Handels in Bezug auf diese beiden Märkte auf Unternehmensebene. Die Daten auf Unternehmensebene zeigen, dass Russland und die Ukraine sowohl am extensiven Rand als auch am intensiven Rand als Handelspartner an Bedeutung verloren haben. Erholungseffekte können seitdem lediglich für den deutsch-ukrainischen Handel beobachtet werden. Innerhalb der Gruppe der Unternehmen, die mit Russland und der Ukraine handeln, zeichnet sich eine deutliche Heterogenität ab, die sich wiederum in der individuellen Vulnerabilität gegenüber den betroffenen Märkten widerspiegelt.
Keywords: 330; Russia; Ukraine; Sanctions; War; Vulnerability; International Trade; Firms; Russland; Ukraine; Sanktionen; Krieg; Verwundbarkeit; Internationaler Handel; Unternehmen